PENGARUH STRUKTUR MODAL DAN MODAL KERJA TERHADAP PROFITABILITAS USAHA PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2016 - Afifatul Uliya; Mulia Andirfa; M. Luthfi Alfahmi (LPPM STIE Lhokseumawe, 2019)
The purpose of this study was to examine the effect of capital structure and working capital simultaneously on business profitability in Coal Mining Companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data, that is time series data for the 2011-2016 period. The data source came from 7 (seven) Coal Mining Companies listed on the Indonesia Stock Exchange from 2011 - 2016. Data processing was carried out using the SPSS program with multiple linear regression equations. The results of the study show that: The capital structure does not affect the profitability of businesses in Coal Mining Companies listed on the Indonesia Stock Exchange. Working capital has a significant effect on business profitability in Coal Mining Companies listed on the Indonesia Stock Exchange. Simultaneously the capital structure and working capital have a significant effect on business profitability in Coal Mining Companies listed on the Indonesia Stock Exchange. Capital structure and working capital have a moderate relationship with business profitability in Coal Mining Companies listed on the Indonesia Stock Exchange. Capital structure and working capital have the ability to explain its effect on business profitability in Coal Mining Companies listed on the Indonesia Stock Exchange by 23%, while the remaining 77% is influenced by other variables outside this research model such as operational costs, production costs, sales volume, and others.